Evaluation of implementation of Regional School Operational Assistance Policy (Bosda) in Anambas Islands District of Riau Islands Province - Atmadinata; Sujanto, Bedjo; Suryadi (Technium Social Sciences Journal, 2020)
The purpose of this research is to see and evaluate a policy that has been implemented by the Anambas Regency, Riau Islands Province regarding regional operational assistance in a school. The research method used in this study is a qualitative research method with interview data collection techniques, surveys and documentation and data analysis techniques used in the study include three streams of activity, namely: data reduction, data presentation (display data), and conclusion / verification (conclusion drawing / verification). The result of this research is that regional operational assistance which is distributed to schools needs to be reviewed because many do not match the portion of the school because the inappropriate amount makes school operational assistance funds large and not on target.